2016
DOI: 10.3892/ijmm.2016.2725
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic effects of rHSG on C6 glioma cells

Abstract: Our previous in vitro study demonstrated that the rat hyperplasia suppressor gene (rHSG) inhibited the proliferation of C6 cells. In the present study, we investigated further the effects of rHSG overexpression on the apoptosis of C6 cells and the possible pathways involved. Hoechst 33342/PI double staining and comet assay were used to examine the morphological characteristics of apoptosis and to examine the effects of rHSG on the apoptosis of the C6 cells. Western blot analysis was used to determine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Gliomas are the most common malignant brain tumors, accounting for ∼50% of all CNS tumors ( Gao et al , 2016 ). Gliomas are characterized by rapid cell growth and diffuse cellular infiltration into adjacent normal tissues ( Ru et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gliomas are the most common malignant brain tumors, accounting for ∼50% of all CNS tumors ( Gao et al , 2016 ). Gliomas are characterized by rapid cell growth and diffuse cellular infiltration into adjacent normal tissues ( Ru et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chrysoeriol-induced apoptosis has been observed in pancreatic cancer (Zhang et al 2018a, b). Western blotting and immunocytochemistry were chosen in this study, because they not only presented the quantification of apoptosis but also showed molecular markers of the signaling pathway (Decrock et al 2009;Gao et al 2016) the same as in HeLa cervical cancer cells (Shi et al 2019) and in HepG2 hepatocellular carcinoma cells (Zhu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The 4‐aminopyridine (4‐ampy) has been studied since the 90s when properties related to glioma treatment were revealed [1] . Glioma accounts for around 50 % of all central nervous system cancers and stands as the prevailing type of brain cancer [2] . Current treatments, which involve a combination of surgery, chemotherapy, and radiotherapy, frequently enhance the survival time of patients suffering from this particular cancer.…”
Section: Introductionmentioning
confidence: 99%